2017
DOI: 10.1038/nplants.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

A footprint of desiccation tolerance in the genome of Xerophyta viscosa

Abstract: Desiccation tolerance is common in seeds and various other organisms, but only a few angiosperm species possess vegetative desiccation tolerance. These 'resurrection species' may serve as ideal models for the ultimate design of crops with enhanced drought tolerance. To understand the molecular and genetic mechanisms enabling vegetative desiccation tolerance, we produced a high-quality whole-genome sequence for the resurrection plant Xerophyta viscosa and assessed transcriptome changes during its dehydration. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
210
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(221 citation statements)
references
References 73 publications
8
210
0
3
Order By: Relevance
“…An analysis of the genome of the resurrection species Xerophyta viscosa, along with transcriptomic changes that occur during desiccation and rehydration, indicated that transcripts typically associated with seed DT were induced, such as homologs of the transcription factor gene ABSCISIC ACID INSENSITIVE3 (ABI3; see Box 1; Costa et al, 2017). The lack of DT-specific genome organizational features in the resurrection species Boea hygrometrica supports the notion that vegetative DT evolved from preexisting genetic modules (Xiao et al, 2015).…”
Section: Information For Crop Improvementmentioning
confidence: 79%
See 4 more Smart Citations
“…An analysis of the genome of the resurrection species Xerophyta viscosa, along with transcriptomic changes that occur during desiccation and rehydration, indicated that transcripts typically associated with seed DT were induced, such as homologs of the transcription factor gene ABSCISIC ACID INSENSITIVE3 (ABI3; see Box 1; Costa et al, 2017). The lack of DT-specific genome organizational features in the resurrection species Boea hygrometrica supports the notion that vegetative DT evolved from preexisting genetic modules (Xiao et al, 2015).…”
Section: Information For Crop Improvementmentioning
confidence: 79%
“…Phylogenetic evidence suggests that vegetative DT in angiosperm resurrection plants represents an adaptation of developmentally regulated DT mechanisms in seeds that have been adjusted to the whole-plant context (Oliver et al, 2000;Illing et al, 2005;Rascio and La Rocca, 2005;Bartels and Hussain, 2011;Farrant and Moore, 2011;Farrant et al, 2015;Costa et al, 2017). Some similarities between seeds and angiosperm resurrection plants have been analyzed in the past (Illing et al, 2005), and the availability of more comprehensive desiccationassociated transcriptomes from resurrection plants (Rodriguez et al, 2010;Bartels and Hussain, 2011;Yobi et al, 2017) linked to sequenced genomes (Xiao et al, 2015;Costa et al, 2017) and seedlings in which DT is reintroduced (Maia et al, 2011;Terrasson et al, 2013;Costa et al, 2015) is allowing the exact mechanisms inherited by these plants to be refined. For example, a cross-species comparison of DT-related transcriptomes revealed a considerable similarity in the genes involved in vegetative DT and seed DT (Costa et al, 2016).…”
Section: Information For Crop Improvementmentioning
confidence: 99%
See 3 more Smart Citations